Contribution to knowledge of Typhlocybinae (Hemiptera: Cicadellidae) in Thailand: first record of genus Arboridia Zachvatkin with description of three new species and a new synonymy - Song, Yue-Hua; Li, Zi-Zhong; Dietrich, Christopher H. (Zootaxa, 2016)
Three new species, Arboridia (Arboridia) magna sp.nov., A. (Arborifera) mira sp.nov. and A. (Arboridia) sexprocessa sp.nov. from Phitsanulok, Thailand are described and illustrated. A key for the identification of species of Arboridia from Thailand is provided. Arboridia (Arboridia) koreana Oh & Jung 2015 is synonymised with A. (Arboridia) agrillacea (Anufriev 1969).